Prediksi Erosi dan Perencanaan Konservasi Tanah dan Air pada Daerah Aliran Sungai Saba - I GUSTI AYU SURYA UTAMI DEWI; NI MADE TRIGUNASIH; TATIEK KUSMAWATI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2012)
ABSTRACT Erosion Prediction and Planning of Soil Water Conservation at Saba Watershed The purpose of this research was to predict the actual erosion (A) at watershed Saba and planning of soil and water conservation when the actual erosion is more than tolerable erosion (EDP) at watershed Saba. The USLE (Universal Soil Loss Equation) was used to predict erosion and planning of soil and water conservation. The result showed that erosion at watershed Saba level was varied from very slight to very severe. The lowest erosion in range 0,16 until 12,32 ton/ha/yr on land unit 1, 2, 27, 28, 29 (Pujungan village), 9, 15 (Pupuan village), 13 (Pucaksari village), 21, 24 (Patemon village), 22 (Ringdikit village), 23 (Pengastulan village) and 25 (Bengkel village), the areas is about 3.337,616 ha (26,19 %). The slight erosion was 37,94 ton/ha/yr on land unit 12 (Bantiran village), the areas is about 399,585 ha (3,14 %). The moderate erosion in range 76,26 until 165,80 ton/ha/yr, on land unit 4, 7, 30 (Pujungan village),10 (Subuk village), 18 (Kedis village), 19 (Bengkel village) and 26 (Patemon village), the areas is about 6.101,079 ha (47,89 %). The severe erosion in range 192,02 until 403,63 ton/ha/yr, on land unit 3, 5 (Pujungan village), 6 (Pupuan village), 14, 20 (Subuk village), 16 (Ularan village) and 17 (Kedis village), the areas is about 1.852,339 ha (14,54 %). The very severe erosion in range 545,97 until 728,60 ton/ha/yr, on land unit 8 (Pujungan village) and 11 (Subuk village ), the areas is about 1.049,935 ha (8,24 %). Planning of soil and water conservation is done by planting cover crops, plant growing storied canopies and constructed terrace. Keywords : prediction of erosion, soil and water conservation planning